2021
DOI: 10.1002/lsm.23360
|View full text |Cite
|
Sign up to set email alerts
|

Channel Interaction During Infrared Light Stimulation in the Cochlea

Abstract: Background and Objectives The number of perceptually independent channels to encode acoustic information is limited in contemporary cochlear implants (CIs) because of the current spread in the tissue. It has been suggested that neighboring electrodes have to be separated in humans by a distance of more than 2 mm to eliminate significant overlap of the electric current fields and subsequent interaction between the channels. It has also been argued that an increase in the number of independent channels could imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In other words, assuming the length over which the electrodes are distributed in contemporary CI electrodes, about 8 (48/5.9) independent channels are expected [56]. This correlates well with the values reported in the literature [57,58].…”
Section: Number Of Stimulation Sitessupporting
confidence: 89%
See 1 more Smart Citation
“…In other words, assuming the length over which the electrodes are distributed in contemporary CI electrodes, about 8 (48/5.9) independent channels are expected [56]. This correlates well with the values reported in the literature [57,58].…”
Section: Number Of Stimulation Sitessupporting
confidence: 89%
“…Power calculations are based on the long term behavioral study in cats [40] and the experiments on channel interaction during optical stimulation in guinea pigs [56]. During the behavioral study, responses were obtained with a 200 pulses/s repetition rate, a 100 µs pulse length, and 12 µJ radiant energy.…”
Section: Power Consumptionmentioning
confidence: 99%
“…The Richter group has worked to exploit the specificity of INS for implantable cochlear prosthetics (Izzo and others 2006). Agarwal and others has reported that the number of optical channels can be twice that of electrical channels, providing promise for greater number of spectral bands and ability to recognize pitch (Agarwal and others 2021). In 2010, a patent (Walsh and others 2010) was approved for a set of implantable optical stimulators of the auditory nerve containing multiple light sources.…”
Section: Translation To Personalized Medicinementioning
confidence: 99%
“…The advantage of using INM over electrical stimulation is that due to its improved spatial selectivity, the optical light delivery is not limited by the same minimum spacing as for electrodes before channel interaction sets in. This can enable a better acoustic resolution by stimulating more independent channels in parallel (associated with more spectral bands), thus improving the richness and clarity of the auditory experience, especially in noisy environments, and for music perception [167].…”
Section: Cochlear Implantsmentioning
confidence: 99%
“…The multi-channel excitation requires close placement of the light sources, which determines the frequency resolution of the auditory response. For such a light delivery system, various options for the optrodes based on fiber, waveguides, arrays of light sources are currently considered to induce a 360 • coverage in a compact size [163,167]. Recently, for a practical implementation, an implantable optrode design based on side-emitting laser diodes was demonstrated [163].…”
Section: Cochlear Implantsmentioning
confidence: 99%